TiO2-SiO2 nanofluids mixture with W/EG for solar water heating system: Thermal conductivity analysis based on different ratios - Mohd Amiruddin, Fikri; Wan Mohcd Faizal, Wan Ishak; Hasyiya Karimah, Adli; Rizalman, Mamat; Wan Azmi, Wan Hamzah; Anwar Ilmar, Ramadhan (AIP Publishing LLC, 2022)
Renewable energy, also considered clean energy, comes from continuously replenishing natural sources and processes. The thermal-physical properties of TiO 2-SiO2, a 60:40 volume ratio of nanoparticles suspended in water (W) and Ethylene Glycol (EG) were investigated. Experiments were carried out to varied mixing ratios of 70:30 and 30:70 for volume concentrations of 0.3 to 0.7 % TiO2-SiO2 nanofluids. The thermal conductivity and dynamic viscosity at from 30 to 70 °C were determined. Taken together, the results showed that the highest thermal conductivity for TiO2-SiO2 nanofluids produced throughout the ratios of 30:70 while 70:30 exhibited the lowest. The nature enhancement ratio indicates that a 0.7 % volume concentration of TiO2-SiO2nanofluid would further facilitate heat transmission throughout all mixture ratios. In comparison with the base fluid, the amalgamation of increased thermal conductivity and dynamic viscosity generates more benefits for heat transmission.